PERANCANGAN DASHBOARD DATA KEPENDUDUKAN DI KABUPATEN BADUNG: DESIGNING A DASHBOARD OF POPULATION DATA IN BADUNG DISTRICT - Ananta Yuda, Putu Danny Satria; Eka Karyawati, Anak Agung Istri Ngurah; Widhi Wirawan, I Made (Jurusan Informatika, Fakultas Matematika dan Ilmu Pengetahuan Alam, Universitas Udayana, 2024)
This journal presents the design and implementation of a population data dashboard for Kabupaten Badung, a rapidly developing region facing the challenge of managing accurate and relevant population data. The Badung Communication and Information Agency (Diskominfo Badung) aims to create an innovative and responsive dashboard to support efficient development planning and public service. The implementation method covers needs analysis, design, socialization, and evaluation, ensuring that the dashboard meets diverse user requirements. The dashboard centralizes population data, providing a comprehensive and real-time overview that empowers stakeholders to make data-driven decisions, contributing to the region's sustainable development and better quality of life. Keywords: data cleaning, dashboard, python, pandas, tableau